2009
DOI: 10.1016/j.jtcvs.2008.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Induction chemoradiotherapy facilitates radical resection of T4 non–small cell lung cancer invading the spine

Abstract: Highly selected patients with lung cancer invading the spine can potentially be cured with induction chemoradiation therapy followed by radical en bloc resection of the tumor. A multidisciplinary operative strategy allows a significant chance of achieving complete resection in patients requiring multilevel hemivertebrectomy or total vertebrectomy and an appreciable cure rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 22 publications
2
25
0
1
Order By: Relevance
“…For instance, in the prior TNM revision, patients with tumors designated as T4 on the basis of invasion were at least staged as IIIB, even those with N0M0 disease. Although these patients were classically considered nonsurgical, successful resection with improved survival has been shown to be possible in select patients with direct invasion of the mediastinum, carina, pulmonary artery, vertebral body, superior vena cava, aorta, and left atrium [41][42][43][44][45][46][47]. These findings support the shift of locally invasive T4 tumors from stage IIIB to IIIA in the absence of N2 or N3 and M1a or M1b disease.…”
Section: Treatment Implicationsmentioning
confidence: 78%
“…For instance, in the prior TNM revision, patients with tumors designated as T4 on the basis of invasion were at least staged as IIIB, even those with N0M0 disease. Although these patients were classically considered nonsurgical, successful resection with improved survival has been shown to be possible in select patients with direct invasion of the mediastinum, carina, pulmonary artery, vertebral body, superior vena cava, aorta, and left atrium [41][42][43][44][45][46][47]. These findings support the shift of locally invasive T4 tumors from stage IIIB to IIIA in the absence of N2 or N3 and M1a or M1b disease.…”
Section: Treatment Implicationsmentioning
confidence: 78%
“…3 Since then, we and others have published results on larger series with encouraging results. [4][5][6][7][8] Nevertheless, data on long-term outcome after these challenging resections remain limited. In this report, we describe our surgical experience and long-term results after multimodality treatment.…”
mentioning
confidence: 99%
“…Grunenwald et al reported the first total vertebrectomy (39). Following these initial reports, several groups have published results (4046), which were summarized in a recent review by Collaud et al (47) (Table 3). In this review of 135 pooled cases, it was noted that 37% of patients received neoadjuvant chemoradiation and 22% received chemotherapy alone.…”
Section: Vertebral Involvementmentioning
confidence: 99%
“…Unsurprisingly, the most significant predictive factor was residual margin (R0 vs. R1). Complete pathologic response to neoadjuvant chemoradiation has been reported to be as high as 48% (40). On the basis of these findings, as well as data on T4 Pancoast tumors, the general consensus is to offer patients induction therapy if vertebral body involvement is suspected.…”
Section: Vertebral Involvementmentioning
confidence: 99%